2023
DOI: 10.3390/polym15071772
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Fractal Dimension, and Texture Analysis of Selected 3D-Printed Resins Used in Dentistry That Underwent the Compression Test

Abstract: Three-dimensional printing is finding increasing applications in today’s world. Due to the accuracy and the possibility of rapid production, the CAD/CAM (computer-aided design/computer-aided manufacturing) technology has become the most desired approach in the preparation of elements, especially in medicine and dentistry. This study aimed to compare the biomechanical properties, fractal dimension (FD), and texture of three selected materials used for 3D printing in dentistry. Three biomaterials used in 3D prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…On the other hand, IBT exhibited the lowest stability, indicating that it may be more suitable for the preparation of imprecise medical elements or auxiliary tools. Dental LT Clear, on the other hand, did not show any changes in texture after the compression test [25]. In a comparative study on BioMed Amber and Dental LT Clear, it was found that both materials are rigid and stable in properties.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, IBT exhibited the lowest stability, indicating that it may be more suitable for the preparation of imprecise medical elements or auxiliary tools. Dental LT Clear, on the other hand, did not show any changes in texture after the compression test [25]. In a comparative study on BioMed Amber and Dental LT Clear, it was found that both materials are rigid and stable in properties.…”
Section: Discussionmentioning
confidence: 88%
“…These results may correspond also to reported changes in fractal dimension (FD) and texture analyses (TA) presented in previous studies. The study showed that Amber resin shows a high number of changes in the fractal and texture analyses [32]. The presented study referred to the compression test only, with no influence of external conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Anna Paradowska-Stolarz et al [ 31 ] studied the texture and mechanical properties of 3-D printed resin and showed less texture changes. The development of surface texture such as ceramic grooves, micro-dimples, microchannels, micro-grids, and micro-pores on the material’s surface using 3D-printing technology would be of significant interest in studying the nature of the material surface.…”
Section: Discussionmentioning
confidence: 99%